BADAN PENGAWAS PEMILU DALAM SISTEM KETATANEGARAAN INDONESIA DALAM PERSPEKTIF KOMUNIKASI POLITIK - Rini Fitria (JURNAL ILMIAH SYI'AR, 2015)
The concept of political communication in the democratic transition towards the establishment of a democratic state often involve new phenomena as the implications of the choice of the nation in building a perception of an open political event . Each country undergoing democratic transition always pass through political processes that may lead to mismanagement of the system due to the country’s political actors involved in - it offers the concept of democracy is based on the background thinking and understanding of each of the idealization of the implementation of a democratic system in the country . Democratic governance envisioned by the citizens of the nation was sometimes must pass through a political transition that is not elegant and often inserted by the political practices of authoritarian power.